Maths-
General
Easy

Question

Solve the following by using the method of substitution
Y = - 2X-3
Y = - X-4

Hint:

find x by substituting y (in terms of x) in the equation and find y by substituting value of  x in the equations  .

The correct answer is: x = 1 and y = - 5


    Ans :- x = 1 ; y = -5
    Explanation :-
    ⇒  y = -2x - 3 — eq 1
    ⇒  y = -x - 4—- eq 2
    Step 1 :- find x by substituting y = 4x + 2 in eq 2.
    -2x - 3 =   -x – 4  ⇒  2x + 3x + 4
    ⇒  2x – x = 4 - 3 ⇒ x  = 4 - 3
    ⇒  x  = 1
    Step 2 :- substitute value of x and find y
    ⇒  y =  - x – 4  ⇒  y = -1 - 4
    ∴  y =  - 5
    ∴   x = 1 and y = - 5  is the solution of the given pair of equations.

    Related Questions to study

    General
    Maths-

    Solve the system of equations by elimination :
    X - 2Y = 1
    2X + 3Y= - 12

    SOLUTION:
    HINT: Perform any arithmetic operation and then find.
    Complete step by step solution:
    Let x - 2y = 1…(i)
    and 2x + 3y=-12….(ii)
    On multiplying (i) with 2, we get 2(x - 2y = 1)
    ⇒ 2x - 4y = 2…(iii)
    Now, we have the coefficients of x in (ii) and (iii) to be the same.
    On subtracting (ii) from (iii),
    we get LHS to be 2x - 4y - (2x + 3y) = - 4y - 3y = - 7y
    and RHS to be 2 - (- 12) = 14
    On equating LHS and RHS, we have - 7y = 14
    ⇒ y = - 2
    On substituting the value of y in (i), we get x - 2 × - 2 =1
    ⇒ x + 4 = 1
    ⇒ x = 1-4
    ⇒ x = - 3
    Hence we get x = - 3 and y = - 2
    Note: We can also solve these system of equations by making the coefficients of y
    to be the same in both the equations

    Solve the system of equations by elimination :
    X - 2Y = 1
    2X + 3Y= - 12

    Maths-General
    SOLUTION:
    HINT: Perform any arithmetic operation and then find.
    Complete step by step solution:
    Let x - 2y = 1…(i)
    and 2x + 3y=-12….(ii)
    On multiplying (i) with 2, we get 2(x - 2y = 1)
    ⇒ 2x - 4y = 2…(iii)
    Now, we have the coefficients of x in (ii) and (iii) to be the same.
    On subtracting (ii) from (iii),
    we get LHS to be 2x - 4y - (2x + 3y) = - 4y - 3y = - 7y
    and RHS to be 2 - (- 12) = 14
    On equating LHS and RHS, we have - 7y = 14
    ⇒ y = - 2
    On substituting the value of y in (i), we get x - 2 × - 2 =1
    ⇒ x + 4 = 1
    ⇒ x = 1-4
    ⇒ x = - 3
    Hence we get x = - 3 and y = - 2
    Note: We can also solve these system of equations by making the coefficients of y
    to be the same in both the equations
    General
    Maths-

    Solve the equation. Write a reason for each step.
    𝑥 − 2 + 3(𝑥 + 2) = 3𝑥 + 10

    HINT – Open the brackets
    SOL – It is given that 𝑥 − 2 + 3(𝑥 + 2) = 3𝑥 + 10
    Opening the brackets
    We get, x – 2 + 3x + 6 = 3x + 10
    rightwards double arrow 4x + 4 = 3x + 10      ( Adding similar terms )
    rightwards double arrow 4x – 3x = 10 – 4
    rightwards double arrow x = 6.

    Solve the equation. Write a reason for each step.
    𝑥 − 2 + 3(𝑥 + 2) = 3𝑥 + 10

    Maths-General
    HINT – Open the brackets
    SOL – It is given that 𝑥 − 2 + 3(𝑥 + 2) = 3𝑥 + 10
    Opening the brackets
    We get, x – 2 + 3x + 6 = 3x + 10
    rightwards double arrow 4x + 4 = 3x + 10      ( Adding similar terms )
    rightwards double arrow 4x – 3x = 10 – 4
    rightwards double arrow x = 6.
    General
    Maths-

    Use Substitution to solve each system of equations :
    6X - 3Y = -6
    Y = 2X + 2

    Solution :-
    Hint :- find x by substituting y (in terms of x) in the equation and find y by substituting value of  x in the equations  .If we get a true statement we say they have infinite solutions .If we get the false statement we say they have no solution.
    Ans :- infinite no.of solutions .
    Explanation :-
    y = 2x + 2— eq 1
    6x - 3y = -6—- eq 2
    Step 1 :- find x by substituting y = 2x + 2 in eq 2.
    6x - 3 (2x + 2) = -6 ⇒ 6 x -6x - 6 = -6
    -6 = -6
    Here we get -6 = -6 which is always true i.e always having a root .
    They coincide with each other and have infinite no.of solutions
    They have infinite no.of solutions for the given system of equations

    Use Substitution to solve each system of equations :
    6X - 3Y = -6
    Y = 2X + 2

    Maths-General
    Solution :-
    Hint :- find x by substituting y (in terms of x) in the equation and find y by substituting value of  x in the equations  .If we get a true statement we say they have infinite solutions .If we get the false statement we say they have no solution.
    Ans :- infinite no.of solutions .
    Explanation :-
    y = 2x + 2— eq 1
    6x - 3y = -6—- eq 2
    Step 1 :- find x by substituting y = 2x + 2 in eq 2.
    6x - 3 (2x + 2) = -6 ⇒ 6 x -6x - 6 = -6
    -6 = -6
    Here we get -6 = -6 which is always true i.e always having a root .
    They coincide with each other and have infinite no.of solutions
    They have infinite no.of solutions for the given system of equations

    parallel
    General
    Maths-

    Given: 𝑚∠𝑃 = 30°, 𝑚∠𝑄 = 30° , 𝑚∠𝑄 = 𝑚∠𝑅
    Prove: 𝑚∠𝑃 ≅ 𝑚∠𝑅 = 30°

    SOL – It is given that 𝑚∠𝑃 = 30° and  𝑚∠𝑄 = 30°

    rightwards double arrow 𝑚∠𝑃 = 𝑚∠𝑄           ---- (1)
    Further, it is given that 𝑚∠𝑄 = 𝑚∠𝑅    ---- (1)
    Using transitive property which states that if A = B and B = C then A = C
    We get from (1) and (2),

    𝑚∠P = 𝑚∠R = 30°
    Hence Proved

    Given: 𝑚∠𝑃 = 30°, 𝑚∠𝑄 = 30° , 𝑚∠𝑄 = 𝑚∠𝑅
    Prove: 𝑚∠𝑃 ≅ 𝑚∠𝑅 = 30°

    Maths-General
    SOL – It is given that 𝑚∠𝑃 = 30° and  𝑚∠𝑄 = 30°

    rightwards double arrow 𝑚∠𝑃 = 𝑚∠𝑄           ---- (1)
    Further, it is given that 𝑚∠𝑄 = 𝑚∠𝑅    ---- (1)
    Using transitive property which states that if A = B and B = C then A = C
    We get from (1) and (2),

    𝑚∠P = 𝑚∠R = 30°
    Hence Proved

    General
    Maths-

    Use the given information and the diagram to prove the statement.
    Given: 𝑚∠𝑃𝑀𝐶 + 𝑚∠𝑃𝑀𝐷 = 180° and 𝑚∠𝑃𝑀𝐶 = 150°
    Prove: 𝑚∠𝑃𝑀𝐷 = 30°

    HINT – Use the information given.
    SOL – It is given that 𝑚∠𝑃𝑀𝐶 = 150°    ---- (1)
    𝑚∠𝑃𝑀𝐶 + 𝑚∠𝑃𝑀𝐷 = 180°
    150° + 𝑚∠𝑃𝑀𝐷 = 180°             ( - From (1) )
    𝑚∠𝑃𝑀𝐷 = 180° - 150°
    = 30°
    Hence Proved.

    Use the given information and the diagram to prove the statement.
    Given: 𝑚∠𝑃𝑀𝐶 + 𝑚∠𝑃𝑀𝐷 = 180° and 𝑚∠𝑃𝑀𝐶 = 150°
    Prove: 𝑚∠𝑃𝑀𝐷 = 30°

    Maths-General
    HINT – Use the information given.
    SOL – It is given that 𝑚∠𝑃𝑀𝐶 = 150°    ---- (1)
    𝑚∠𝑃𝑀𝐶 + 𝑚∠𝑃𝑀𝐷 = 180°
    150° + 𝑚∠𝑃𝑀𝐷 = 180°             ( - From (1) )
    𝑚∠𝑃𝑀𝐷 = 180° - 150°
    = 30°
    Hence Proved.
    General
    Maths-

    Solve the system of equations by elimination :
    3X + 2Y = 8
    X + 4Y = - 4

    Complete step by step solution:
    Let 3x + 2y = 8…(i)
    and x + 4y = - 4….(ii)
    On multiplying (ii) with 3, we get 3(x + 4y=-4)
    ⇒3x + 12y = - 12…(iii)
    Now, we have the coefficients of  in (i) and (iii) to be the same.
    On subtracting (i) from (iii),
    we get LHS to be 3x + 12y - (3x + 2y) = 12y - 2y = 10y
    and RHS to be - 12 - 8 = - 20
    On equating LHS and RHS, we have 10y = - 20
    ⇒y = - 2
    On substituting the value of y in (i), we get 3x + 2× - 2 = 8
    ⇒ 3x - 4 = 8
    ⇒ 3x = 8 + 4
    ⇒ 3x = 12
    ⇒x = 4
    Hence we get x = 4 and y = - 2
    Note: We can also solve these system of equations by making the coefficients of y
    to be the same in both the equations

    Solve the system of equations by elimination :
    3X + 2Y = 8
    X + 4Y = - 4

    Maths-General
    Complete step by step solution:
    Let 3x + 2y = 8…(i)
    and x + 4y = - 4….(ii)
    On multiplying (ii) with 3, we get 3(x + 4y=-4)
    ⇒3x + 12y = - 12…(iii)
    Now, we have the coefficients of  in (i) and (iii) to be the same.
    On subtracting (i) from (iii),
    we get LHS to be 3x + 12y - (3x + 2y) = 12y - 2y = 10y
    and RHS to be - 12 - 8 = - 20
    On equating LHS and RHS, we have 10y = - 20
    ⇒y = - 2
    On substituting the value of y in (i), we get 3x + 2× - 2 = 8
    ⇒ 3x - 4 = 8
    ⇒ 3x = 8 + 4
    ⇒ 3x = 12
    ⇒x = 4
    Hence we get x = 4 and y = - 2
    Note: We can also solve these system of equations by making the coefficients of y
    to be the same in both the equations
    parallel
    General
    Maths-

    Give a two-column proof.
    Given:

    Prove: PR = 25 in

    HINT – Use Segment Addition Postulate
    SOL – In the given figure, line segment has two end points namely P and R and Q is lying on the line segment PR
    rightwards double arrow PR = PQ + QR
    rightwards double arrow PR = 12 + 13
    rightwards double arrow PR = 25 in.
    Hence Proved.

    Give a two-column proof.
    Given:

    Prove: PR = 25 in

    Maths-General
    HINT – Use Segment Addition Postulate
    SOL – In the given figure, line segment has two end points namely P and R and Q is lying on the line segment PR
    rightwards double arrow PR = PQ + QR
    rightwards double arrow PR = 12 + 13
    rightwards double arrow PR = 25 in.
    Hence Proved.
    General
    Maths-

    Use Substitution to solve each system of equations :
    - 3X - Y = 7
    X + 2Y = 6

    Solution :-
    Hint :- find x by substituting y (in terms of x) in the equation and find y by substituting value of  x in the equations.
    Ans :- x = -4; y = 5
    Explanation :-
    3x - y = 7 ⇒ - 3x - 7 = y                     — eq 1
    x + 2y = 6                                     —- eq 2
    x + 2 ( - 3x - 7) = 6 ⇒ x - 6x - 14 = 6
    ⇒ - 5x = 14 + 6 ⇒ - 5x = 20
    ⇒ x = -4
    Step 2 :- substitute value of x and find y
    ⇒ - 3x - 7 = y ⇒ y = - 3 (- 4) - 7
    ⇒ y = 12 - 7
    ∴ y = 5
    x = -4 and y = 5 is the solution of the given pair of equations.


    Use Substitution to solve each system of equations :
    - 3X - Y = 7
    X + 2Y = 6

    Maths-General
    Solution :-
    Hint :- find x by substituting y (in terms of x) in the equation and find y by substituting value of  x in the equations.
    Ans :- x = -4; y = 5
    Explanation :-
    3x - y = 7 ⇒ - 3x - 7 = y                     — eq 1
    x + 2y = 6                                     —- eq 2
    x + 2 ( - 3x - 7) = 6 ⇒ x - 6x - 14 = 6
    ⇒ - 5x = 14 + 6 ⇒ - 5x = 20
    ⇒ x = -4
    Step 2 :- substitute value of x and find y
    ⇒ - 3x - 7 = y ⇒ y = - 3 (- 4) - 7
    ⇒ y = 12 - 7
    ∴ y = 5
    x = -4 and y = 5 is the solution of the given pair of equations.


    General
    Maths-

    If Q is the midpoint of PR, prove that PR = 2 PQ.
    Give a two-column proof.

    HINT – Use Segment Addition Postulate
    SOL – If Q is mid – point  Þ PQ = QR      ---- (1)
    Using Segment Addition Postulate,
    We get,  PR = PQ + QR
    rightwards double arrow PR = PQ + PQ
    rightwards double arrow PR = 2 PQ
    Hence Proved.

    If Q is the midpoint of PR, prove that PR = 2 PQ.
    Give a two-column proof.

    Maths-General
    HINT – Use Segment Addition Postulate
    SOL – If Q is mid – point  Þ PQ = QR      ---- (1)
    Using Segment Addition Postulate,
    We get,  PR = PQ + QR
    rightwards double arrow PR = PQ + PQ
    rightwards double arrow PR = 2 PQ
    Hence Proved.
    parallel
    General
    Maths-

    Compare 𝑚∠𝑃𝑂𝑄𝑎𝑛𝑑∠𝑆𝑂𝑇.

    • Step by step explanation: 
      • Step 1:
      • Find POQ:
    • Align the protractor with the ray OP on 0o as shown above. 
    • Start reading the inner scale from the 0°.
    • Step 2:
    • From the figure we can see that ray OP is aligned on mark 0o. And ray OQ is aligned on mark 30o.
    Hence, the measure of POQ = (30o - 0o).
    POQ = 30o.
    • Step 3:
    • Find SOT:
      • Align the protractor with the ray OT on 0o as shown above. 
      • Start reading the outer scale from the 0°.
      • Step 4:
      • From the figure we can see that ray OT is aligned on mark 0o. And the ray OS is aligned on mark 20o.
    Hence, the measure of SOT = 20o.

    SOT = 20o.

    • Step 5:
    • Compare ∠POQ and ∠SOT
    Hence, ∠POQ is greater than ∠SOT by 10o.
    • Final Answer:
    Hence, ∠POQ is greater than ∠SOT by 10o.

    Compare 𝑚∠𝑃𝑂𝑄𝑎𝑛𝑑∠𝑆𝑂𝑇.

    Maths-General
    • Step by step explanation: 
      • Step 1:
      • Find POQ:
    • Align the protractor with the ray OP on 0o as shown above. 
    • Start reading the inner scale from the 0°.
    • Step 2:
    • From the figure we can see that ray OP is aligned on mark 0o. And ray OQ is aligned on mark 30o.
    Hence, the measure of POQ = (30o - 0o).
    POQ = 30o.
    • Step 3:
    • Find SOT:
      • Align the protractor with the ray OT on 0o as shown above. 
      • Start reading the outer scale from the 0°.
      • Step 4:
      • From the figure we can see that ray OT is aligned on mark 0o. And the ray OS is aligned on mark 20o.
    Hence, the measure of SOT = 20o.

    SOT = 20o.

    • Step 5:
    • Compare ∠POQ and ∠SOT
    Hence, ∠POQ is greater than ∠SOT by 10o.
    • Final Answer:
    Hence, ∠POQ is greater than ∠SOT by 10o.
    General
    Maths-

    Which postulate will you use to prove that PR = PQ + QR?

    HINT – Try to recall definition of postulates/properties given in options.
    SOL – Option (b)
    Segment addition postulate – It states that if a line segment has two endpoints, A and C, a third point B lies on the line segment AC if and only if this equation AB + BC = AC
    Since in figure given above, line segment has two end points namely P and R and third point Q lies on the line segment PR Þ PR = PQ + QR

    Which postulate will you use to prove that PR = PQ + QR?

    Maths-General
    HINT – Try to recall definition of postulates/properties given in options.
    SOL – Option (b)
    Segment addition postulate – It states that if a line segment has two endpoints, A and C, a third point B lies on the line segment AC if and only if this equation AB + BC = AC
    Since in figure given above, line segment has two end points namely P and R and third point Q lies on the line segment PR Þ PR = PQ + QR
    General
    Maths-

    Solve the system of equations by elimination :
    X - 2Y = - 2
    3X + 2Y = 30

    SOLUTION:
    HINT: Perform any arithmetic operation and then find.
    Complete step by step solution:
    Let x - 2y = - 2…(i)
    and 3x + 2y = 30….(ii)
    On adding (i) and (ii),
    we get LHS to be x - 2y + 3x + 2y = 4x
    and RHS to be -2+ 30 = 28
    On equating LHS and RHS, we get 4x = 28
    ⇒ x = 7
    On substituting the value of x in (i), we get 7 - 2y = - 2
    ⇒ - 2y = - 2 - 7
    ⇒ - 2y = - 9
    ⇒ y =9 over 2
    Hence we get x = 7 and y equals 9 over 2
    Note: We can also solve these system of equations by making the coefficients of x
    to be the same in both the equations.

    Solve the system of equations by elimination :
    X - 2Y = - 2
    3X + 2Y = 30

    Maths-General
    SOLUTION:
    HINT: Perform any arithmetic operation and then find.
    Complete step by step solution:
    Let x - 2y = - 2…(i)
    and 3x + 2y = 30….(ii)
    On adding (i) and (ii),
    we get LHS to be x - 2y + 3x + 2y = 4x
    and RHS to be -2+ 30 = 28
    On equating LHS and RHS, we get 4x = 28
    ⇒ x = 7
    On substituting the value of x in (i), we get 7 - 2y = - 2
    ⇒ - 2y = - 2 - 7
    ⇒ - 2y = - 9
    ⇒ y =9 over 2
    Hence we get x = 7 and y equals 9 over 2
    Note: We can also solve these system of equations by making the coefficients of x
    to be the same in both the equations.
    parallel
    General
    Maths-

    Solve the following by using the method of substitution
    Y = 4X+2
    Y = X+8

    Solution :-
    Hint :- find x by substituting y (in terms of x) in the equation and find y by substituting value of  x in the equations  .
    Ans :- x = 2 ; y =10
    Explanation :-
    ⇒  y =  4x + 2 — eq 1
    ⇒  y  = x + 8—- eq 2
    Step 1 :- find x by substituting  y = 4x + 2 in eq 2.
    4x + 2 = x + 8 ⇒  4x – x = 8 - 2
    ⇒  3x = 8  - 2  ⇒ 3x = 6
    ⇒ x =2
    Step 2 :- substitute value of x and find y
    ⇒  y =  x + 8 ⇒ y = 2 + 8
    ∴ y= 10
    ∴  x = 2 and y = 10  is the solution of the given pair of equations.

    Solve the following by using the method of substitution
    Y = 4X+2
    Y = X+8

    Maths-General
    Solution :-
    Hint :- find x by substituting y (in terms of x) in the equation and find y by substituting value of  x in the equations  .
    Ans :- x = 2 ; y =10
    Explanation :-
    ⇒  y =  4x + 2 — eq 1
    ⇒  y  = x + 8—- eq 2
    Step 1 :- find x by substituting  y = 4x + 2 in eq 2.
    4x + 2 = x + 8 ⇒  4x – x = 8 - 2
    ⇒  3x = 8  - 2  ⇒ 3x = 6
    ⇒ x =2
    Step 2 :- substitute value of x and find y
    ⇒  y =  x + 8 ⇒ y = 2 + 8
    ∴ y= 10
    ∴  x = 2 and y = 10  is the solution of the given pair of equations.
    General
    Maths-

    If lines l and m are parallel, find the value of x.

    SOLUTION:
    HINT: Use the property of parallel lines angle rules.
    Complete step by step solution:
    Here we have 2 parallel lines m and land a transversal intersecting these parallel
    lines.
    Here,  left parenthesis 5 x minus 15 right parenthesis to the power of ring operator text  and  end text 35 to the power of ring operator forms co-interior angles and they add up to 180 to the power of ring operator
    left parenthesis 5 x minus 15 right parenthesis to the power of ring operator plus 35 to the power of ring operator equals 180 to the power of ring operator(co-interior angles)
    not stretchy rightwards double arrow 5 x plus 20 to the power of ring operator equals 180 to the power of ring operator
    not stretchy rightwards double arrow 5 x equals 180 to the power of ring operator minus 20 to the power of ring operator
    not stretchy rightwards double arrow 5 x equals 160 to the power of ring operator
    not stretchy rightwards double arrow x equals 32 to the power of ring operator
    Hence the value of x equals 32 to the power of ring operator

    If lines l and m are parallel, find the value of x.

    Maths-General
    SOLUTION:
    HINT: Use the property of parallel lines angle rules.
    Complete step by step solution:
    Here we have 2 parallel lines m and land a transversal intersecting these parallel
    lines.
    Here,  left parenthesis 5 x minus 15 right parenthesis to the power of ring operator text  and  end text 35 to the power of ring operator forms co-interior angles and they add up to 180 to the power of ring operator
    left parenthesis 5 x minus 15 right parenthesis to the power of ring operator plus 35 to the power of ring operator equals 180 to the power of ring operator(co-interior angles)
    not stretchy rightwards double arrow 5 x plus 20 to the power of ring operator equals 180 to the power of ring operator
    not stretchy rightwards double arrow 5 x equals 180 to the power of ring operator minus 20 to the power of ring operator
    not stretchy rightwards double arrow 5 x equals 160 to the power of ring operator
    not stretchy rightwards double arrow x equals 32 to the power of ring operator
    Hence the value of x equals 32 to the power of ring operator
    General
    Maths-


    Prove that: PR = PQ + QR
    Give a two-column proof

    HINT – Use Euclid’s Axiom
    SOL – In the figure, we can see that PR coincides with
    PQ + QR.
    Acc. to Euclid’s Axiom, things which coincide with one another are equal to one another.
    Hence Proved
    NOTE – Alternative method
    We can also prove using Segment addition postulate which states that if a line segment has two endpoints, A and C, a third point B lies on the line segment AC if and only if this equation AB + BC = AC
    Since in figure given above, Q lies on the line segment PR Þ PR = PQ + QR.


    Prove that: PR = PQ + QR
    Give a two-column proof

    Maths-General
    HINT – Use Euclid’s Axiom
    SOL – In the figure, we can see that PR coincides with
    PQ + QR.
    Acc. to Euclid’s Axiom, things which coincide with one another are equal to one another.
    Hence Proved
    NOTE – Alternative method
    We can also prove using Segment addition postulate which states that if a line segment has two endpoints, A and C, a third point B lies on the line segment AC if and only if this equation AB + BC = AC
    Since in figure given above, Q lies on the line segment PR Þ PR = PQ + QR.
    parallel

    card img

    With Turito Academy.

    card img

    With Turito Foundation.

    card img

    Get an Expert Advice From Turito.

    Turito Academy

    card img

    With Turito Academy.

    Test Prep

    card img

    With Turito Foundation.